The Roles of HIF-1α in Radiosensitivity and Radiation-Induced Bystander Effects Under Hypoxia - Zhang, Jianghong; Zhang, Yuhong; Mo, Fang; Patel, Gaurang; Butterworth, Karl; Shao, Chunlin; Prise, Kevin M. (Frontiers in Cell and Developmental Biology, 2021)
Radiation-induced bystander effects (RIBE) may have potential implications for radiotherapy, yet the radiobiological impact and underlying mechanisms in hypoxic tumor cells remain to be determined. Using two human tumor cell lines, hepatoma HepG2 cells and glioblastoma T98G cells, the present study found that under both normoxic and hypoxic conditions, increased micronucleus formation and decreased cell survival were observed in non-irradiated bystander cells which had been co-cultured with X-irradiated cells or treated with conditioned-medium harvested from X-irradiated cells. Although the radiosensitivity of hypoxic tumor cells was lower than that of aerobic cells, the yield of micronucleus induced in bystander cells under hypoxia was similar to that measured under normoxia indicating that RIBE is a more significant factor in overall radiation damage of hypoxic cells. When hypoxic cells were treated with dimethyl sulfoxide (DMSO), a scavenger of reactive oxygen species (ROS), or aminoguanidine (AG), an inhibitor of nitric oxide synthase (NOS), before and during irradiation, the bystander response was partly diminished. Furthermore, when only hypoxic bystander cells were pretreated with siRNA hypoxia-inducible factor-1α (HIF-1α), RIBE were decreased slightly but if irradiated cells were treated with siRNA HIF-1α, hypoxic RIBE decreased significantly. In addition, the expression of HIF-1α could be increased in association with other downstream effector molecules such as glucose transporter 1 (GLUT-1), vascular endothelial growth factor (VEGF), and carbonic anhydrase (CA9) in irradiated hypoxic cells. However, the expression of HIF-1α expression in bystander cells was decreased by a conditioned medium from isogenic irradiated cells. The current results showed that under hypoxic conditions, irradiated HepG2 and T98G cells showed reduced radiosensitivity by increasing the expression of HIF-1α and induced a syngeneic bystander effect by decreasing the expression of HIF-1α and regulating its downstream target genes in both the irradiated or bystander cells.